ANALISIS PENGEMBANGAN APLIKASI DIGITAL EMPLOYEE DI RSU MUHAMMADIYAH METRO - Aprilianingsih, Maya; Putra, Yogi Catur; Mutiara Az-Zahra; Firnanda Elgi Taura; Barokah Kurnia Sari; Selvianingsih; Fitri Cahya Bintang; Azwar Amien Tohari; Andini Riska Dewani; Viska Oktaviana (Journal of Hospital Administration and Excellent Health Service, 2025)
Introduction : This report presents the results of the Field Learning Experience (PBL) conducted by undergraduate students of the Hospital Administration Program at Universitas Muhammadiyah Metro at RSU Muhammadiyah Metro from May 14 to May 27, 2025. The main focus of this activity was to analyze the development and implementation of a digital employee application feature—specifically digital archiving—as a solution to the manual personnel record management issues within the Human Resource Unit (SDI). Manual archiving was found to be inefficient due to risks such as document damage, data loss, and delays in administrative processes.The methods used included direct observation, interviews with unit heads, collection of primary and secondary data, and Focus Group Discussions (FGDs). Problem identification was conducted across several units such as Public Relations, Household Logistics, Pharmacy, Human Resources, and Medical Records. Priority analysis using the Urgency, Seriousness, and Growth (USG) method identified the manual archiving issue in the HR unit as the top priority.The proposed solution involves adding a digital archiving feature to the existing employee application to enhance administrative efficiency. This feature enables document categorization, keyword-based search, uploading of various file formats, and includes user authentication and access control for data security. The implementation of digital archiving is expected to modernize hospital governance, improve access to information, and enhance the overall quality of human resource services.